10.6k views
0 votes
A line passes through the points (−4,−9)

and (−2,−6) What is the equation of the line in Slope-Intercept Form?

A line passes through the points (−4,−9) and (−2,−6) What is the equation of the line-example-1
A line passes through the points (−4,−9) and (−2,−6) What is the equation of the line-example-1
A line passes through the points (−4,−9) and (−2,−6) What is the equation of the line-example-2

2 Answers

3 votes

Final answer:

The equation of the line in slope-intercept form that passes through the points (-4, -9) and (-2, -6) is y = 1.5x - 3.

Step-by-step explanation:

In Mathematics

, the equation of a line can be determined using the

Slope-Intercept Form

which is expressed as y = mx + c, where 'm' represents the slope of the line and 'c' is the y-intercept.

To calculate the slope (m), we use the formula: m = (y2 - y1) / (x2 - x1). Plugging in the values of your points which are (-4, -9) as (x1, y1) and (-2, -6) as (x2, y2), we get: m = (-6 - (-9)) / (-2 - (-4)) = 1.5.

Once we have the slope, we can find the y-intercept 'c' by rearranging the line equation to: c = y - mx and substituting in the values of one of the points and the slope (let's use first point (-4, -9)). Thus, c = -9 - 1.5*-4 = -3.

Therefore, our final equation of the line in slope-intercept form is: y = 1.5x - 3.

Learn more about Slope-Intercept Form

User Niitaku
by
5.7k points
0 votes

Answer:

D.
y - 5= 3(x - 1)

B.
y = (3)/(2)x - 3

Step-by-step explanation:

Problem 1:

Point-slope form equation is given as
y - y_1 = m(x - x_1), where, (x1, y1) is a point on the line, and m = slope.

Find the slope of the line of the graph given, using 2 points on the line, points (0, 2) and (1, 5).


m = (y_2 - y_1)/(x_2 - x_1) = (2 - 5)/(0 - 1) = (-3)/(-1) = 3

Substitute (x1, y1) = (1, 5) and m = 3 into
y - y_1 = m(x - x_1)


y - 5= 3(x - 1)

The answer is D.

Problem 2:

Slope-intercept equation takes the form:
y = mx + b, where, m = slope, and b = y-intercept.

Find m and b.

Given, points (−4,−9) and (−2,−6),


slope(m) = (y_2 - y_1)/(x_2 - x_1) = (-6 -(-9))/(-2 -(-4)) = (3)/(2) = (3)/(2)

Substitute x = -2, y = -6, and m = ³/2 into
y = mx + b, to find b:


-6 = (3)/(2)(-2) + b,

Subtract b from both sides


-6 = -3 + b

Add 3 to both sides


-6 + 3 = b


-3 = b


b = -3

Substitute m = ³/2, b = -3 into
y = mx + b


y = (3)/(2)x + (-3)


y = (3)/(2)x - 3

The answer is B.

User Sorabh Mendiratta
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.